Proporsi Perencanaan Kebutuhan SDM Di Unit Kerja Rekam Medis Rumah Sakit Umum Asy Syifa' Sambi - Wahyu Wijaya Widiyanto; Fitria Rohmatun W; Inka Sasti; Salsa Bila Karin (Universitas Duta Bangsa Surakarta, 2021)
The workload in one unit is basically a balance between the quantity and quality of work required of employees with the amount of personnel in the unit. The research method used by distributing questionnaires using google from to the Asy Syifa' Sambi General Hospital officers, while the purpose of this study is to determine the proportion of the workload of health workers using WISN. Based on the calculation of the workforce needs using the WISN method in the correspondence and evaluation section of the Asy Syifa' Sambi General Hospital KLPCM in 2019 from the basic quantity per year divided by the standard workload per year, it was found that the workforce needs in the section receiving requests for filling out medical resumes and or Doctor's Certificate for insurance of 0.5 officers, assembling inpatient DRM and other assessments, registering DRM RI 1.3 officers, receiving requests for Visum et Repertum 0.3 officers, Letter of replacement for Birth Certificate and Legalization of death certificates 0.3 officers , prepare a request for an autopsy of death from the health center / other agencies 0.5 officers. So the total need for KLPCM correspondence and evaluation workers is 3 officers. In fact, in the correspondence and evaluation of KLPCM, there is 1 officer. So it is necessary to add 2 officers, so that they can help ease the workload of other officers so that the work is completed quickly and does not pile up again.